Effect of paeonol on proliferation, apoptosis, migration, invasion and glutamine of gastric cancer cells via circSFMBT2/miR-665 axis - Li, Jia; Zhang, Gang; Wu, Guoqiang (Cellular and Molecular Biology, 2020)
This experiment was performed to investigate the effect of paeonol on the proliferation, apoptosis, migration, invasion and glutamine of gastric cancer HGC-27 cells and its possible mechanism. For this purpose, the MTT method was used to detect cell viability; Flow cytometry experiment was used to detect cell apoptosis; Transwell chamber experiment was used to detect cell migration and invasion; Western blotting was used to detect the expression levels of MMP2 and MMP9 protein; The decomposition of glutamine was evaluated by detecting the expression levels of glutamine, glutamic acid and Î±-ketoglutarate (Î±-KG). This study used RT-PCR to detect the expression of circSFMBT2 and miR-665. The targeting relationship between circSFMBT2 and miR-665 was verified by the dual-luciferase report experiment and RIP experiment. Results showed that different concentrations of Paeonol could significantly inhibit the proliferation, migration, invasion and glutamine decomposition of HGC-27 cells, and induce cell apoptosis in a dose-dependent manner. In gastric cancer tissues and cells, the expression of circSFMBT2 was up-regulated, and the expression of miR-665 was down-regulated. Over-expression of circSFMBT2 could partially restore the effects of paeonol on the proliferation, apoptosis, migration, invasion and glutamine of HGC-27 cells. CircSFMBT2 could target and negatively regulate the expression of miR-665. Overexpression of miR-665 could partially restore the effects of Pae and circSFMBT2 on the proliferation, apoptosis, migration, invasion and glutamine of HGC-27 cells. It was concluded that paeonol can inhibit the proliferation, migration, invasion and glutamine decomposition of gastric cancer HGC-27 cells via circSFMBT2/miR-665 axis, and also induce cell apoptosis.